VALUE–BASED TOTAL PERFORMANCE EXCELLENCE MODEL: AN OVERVIEW (Sains Humanika, 2010)
Today, organizations are competing for the survival. They adopt various performance management systems that best suit their undertakings. There are many performance models which lean towards measuring tangible aspects such as Malcolm Baldridge National Quality Award (MBNQA), European Quality Award (EQA), Deming Prize and Kanji’s Model. However, the measurements of intangible aspects are also important and should be heeded to optimize the organizational performance. This paper discusses the preliminary implementation of the Performance Measurement System (PMS) which showcases an overview of intangible aspects i.e. organizational core values through Value–Based Total Performance Excellence Model (VBTPEM) and identification of existing core values in Malaysian universities. This model will reveal overall standings and achievements of the public universities and indicate opportunities for further improvements based on the value–based indicators.
Keywords: Performance management system; Value–Based Total Performance Excellence Model (VBTPEM)